Application of bacteriocin-producing Enterococcus faecium isolated from donkey milk, in the bio-control of Listeria monocytogenes in fresh whey cheese. (October 2017) - Aspri, Maria; O'Connor, Paula M.; Field, Des; Cotter, Paul D.; Ross, Paul; Hill, Colin; Papademas, Photis
Abstract: A total of 79 bacterial strains, previously isolated from donkey milk, were screened for their antimicrobial activity against several spoilage and foodborne pathogenic bacteria. Amongst them, 3 strains belonging to Enterococcus faecium displayed antimicrobial activity against Listeria monocytogenes, Staphylococcus aureus and Bacillus cereus . Mass spectrometry analysis demonstrated that all enterococci used in this study produced peptides with masses consistent with those for enterocins A and B. The cell-free supernatants of the identified bacteriocin-producing enterococci were equally active over a wide range of pH and heat treatments making them excellent candidates for potential applications in bio-preservation. Bacteriocins produced by these strains were tested for their capability to control post-processing contamination and growth of L. monocytogenes during refrigerated storage of artificially contaminated fresh whey cheese. One strain was considered bactericidal while the other two were classified as bacteriostatic.